2022
DOI: 10.1016/j.crchbi.2022.100021
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on therapeutic potentials of gold and silver nanobiomaterials for human viral diseases

Abstract: Viral diseases are prominent among the widely spread infections threatening human well-being. Real-life clinical successes of the few available therapeutics are challenged by pathogenic resistance and suboptimal delivery to target sites. Nanotechnology has aided the design of functionalised and non-functionalised Au and Ag nanobiomaterials through physical, chemical and biological (green synthesis) methods with improved antiviral efficacy and delivery. In this review, innovative designs, as well as interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Consequently, AgNPs have exhibited a growing ability to penetrate various human body tissues, cells, and biological molecules (Mehwish et al, 2021). Notably, AgNPs have demonstrated promising therapeutic potential in parasitic diseases that specifically target certain cells or organs (Ayipo et al, 2022). For instance, in vitro studies have revealed significant interactions between different concentrations of AgNPs and T. spiralis adults and larvae, leading to cuticle degeneration, which could potentially impede their in vivo binding ability to host cells (Khalifa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, AgNPs have exhibited a growing ability to penetrate various human body tissues, cells, and biological molecules (Mehwish et al, 2021). Notably, AgNPs have demonstrated promising therapeutic potential in parasitic diseases that specifically target certain cells or organs (Ayipo et al, 2022). For instance, in vitro studies have revealed significant interactions between different concentrations of AgNPs and T. spiralis adults and larvae, leading to cuticle degeneration, which could potentially impede their in vivo binding ability to host cells (Khalifa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%